IMPROVING THE OPERATIONAL EFFICIENCY OF THE ORGANIZATION WITH THE USE OF TOOLS AND METHODS OF PROCESS MINING - I. Abdullayev (Стратегии бизнеса, 2019)
This article discusses the introduction of Process Mining methods in the activities of organizations. Process Mining should be used in any cases where there is a reflection of the activities of employees in information systems and where one of two conditions is met: • these are simple mass processes that are produced several thousand (tens of thousands, hundreds of thousands) times a day (for example, customer banking). The sequence of steps is verified to the last detail, and we monitor the effectiveness of a particular employee, Department. It is unlikely that it will be possible to change the mechanics of the process, but you can save on debugging the work of each link, which together will give a tangible effect. • these are complex, long, individual processes involving multiple departments. In this case, Process Mining is not looking for a way to speed up, but a way to simplify the process, optimize the number of steps, avoid process defects, unnecessary cycles, involvement of unnecessary participants, etc. The article shows that in both cases the use of Process Mining gives a significant economic effect.